Rethinking Domestic Debt: Implications for Indonesia's Financial Sector - Sekarani, R.A. Aisyah Fathia; Sugema, Iman; Pasaribu, Syamsul Hidayat (Jurnal Ekonomi Pembangunan, 2024)
Financial development performance can be affected by using domestic debt to address the public sector financing deficit, especially in countries like Indonesia where the financial sector is highly dependent on one subsector while others are still in their infancy. This study investigates Indonesia’s financial development as affected by domestic public debt using secondary time series data from 2010Q1 to 2020Q3. The study employs Principal Component Analysis and Ordinary Least Squares regression models. The findings show that increasing domestic public debt has a positive and significant impact on financial development in Indonesia. Furthermore, it is revealed that domestic public debt positively and significantly affects financial activity and financial size but has a negative and significant impact on financial efficiency. Therefore, the government should consider reducing securitized debt instruments, especially those issued to the banking system, as this may hinder financial development in the long run.